Lead-acid battery

By incorporating an organic antishrinkage agent with specific aromatic compound units into the negative electrode material of lead-acid batteries, the flow of carbonaceous material into the electrolyte is suppressed, improving the battery's performance and stability.

JP7666326B2Active Publication Date: 2025-04-22GS YUASA CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021548956
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-27
Filing Date
2020-09-24
Publication Date
2025-04-22
Estimated Expiration
2040-09-24

AI Technical Summary

Technical Problem

In lead-acid batteries, the flow of carbonaceous material from the negative electrode material into the electrolyte is a significant issue, especially as the content of carbonaceous material in the negative electrode material increases.

Method used

The use of a negative electrode material that includes an organic antishrinkage agent and a carbonaceous material, where the organic inhibitor comprises units of bisarene compounds and monocyclic aromatic compounds with hydroxy groups, specifically bisphenol S or bisphenol A compounds, and phenol sulfonic acid compounds, effectively suppresses the flow of carbonaceous material into the electrolyte.

Benefits of technology

This configuration significantly reduces the flow of carbonaceous material from the negative electrode into the electrolyte, maintaining a high antishrinkage effect and enhancing the battery's low-temperature high-rate discharge performance and charge acceptance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666326000003
    Figure 0007666326000003
  • Figure 0007666326000001
    Figure 0007666326000001
  • Figure 0007666326000002
    Figure 0007666326000002
Patent Text Reader

Abstract

This lead-acid battery is provided with a positive electrode plate, a negative electrode plate, and an electrolyte solution. The negative electrode plate comprises a negative electrode material. The negative electrode material comprises an organic shrinkproofing agent and a carbonaceous material. The organic shrinkproofing agent comprises a unit of a bisarene compound and a unit of a monocyclic aromatic compound having a hydroxy group. The unit of the bisphenol compound is at least one selected from the group consisting of a unit of a bisphenol S compound and a unit of a bisphenol A compound.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a lead-acid battery. [Background technology]

[0002] Lead-acid batteries are used in various applications, including automotive and industrial applications. Lead-acid batteries include a negative electrode plate, a positive electrode plate, and an electrolyte. The negative electrode plate includes a current collector and a negative electrode material. An organic shrinkage inhibitor is added to the negative electrode material. As the organic shrinkage inhibitor, in addition to naturally occurring organic shrinkage inhibitors such as sodium lignin sulfonate, synthetic organic shrinkage inhibitors are also used. As the synthetic organic shrinkage inhibitor, for example, a bisphenol condensate can be mentioned.

[0003] Patent Document 1 describes a lead-acid battery including a positive electrode, a negative electrode, and an electrolyte, in which the negative electrode has a negative electrode material and a negative electrode current collector, the negative electrode material contains a bisphenol resin and a negative electrode active material, the negative electrode current collector has a lug portion, and the lug portion is formed with a surface layer of Sn or a Sn alloy.

[0004] Patent Document 2 describes a flooded lead-acid battery comprising a negative electrode active material mainly composed of sponge lead, a positive electrode active material mainly composed of lead dioxide, and a freely flowing electrolyte solution containing sulfuric acid, wherein the negative electrode active material contains carbon, at least one material selected from the group consisting of cellulose ether, polycarboxylic acid, and salts thereof, and a water-soluble polymer made of a bisphenol-based condensate having a sulfonic acid group, and the positive electrode active material contains antimony.

[0005] Patent Document 3 describes a flooded lead-acid battery comprising a negative electrode active material mainly composed of sponge lead, a positive electrode active material mainly composed of lead dioxide, and a freely flowing electrolyte containing sulfuric acid, wherein the negative electrode active material contains, per 100 mass% of the sponge lead in a chemically-formed state, 0.5 mass% to 2.5 mass% of carbon black, a water-soluble polymer made of a bisphenol-based condensate having a sulfonic acid group as a substituent, and at least one polycarboxylic acid compound selected from the group consisting of polyacrylic acid, polymethacrylic acid, and polymaleic acid and their salts, and the electrolyte has a carbon black concentration of 3 massppm or less in a chemically-formed state.

[0006] Patent Document 4 describes a negative electrode plate for a lead-acid battery, which is composed of a negative electrode active material mainly composed of sponge lead and a current collector, in which the negative electrode active material, after being chemically formed, contains 1.0 mass% or more and 2.5 mass% or less of carbon black and 0.1 mass% or more and 0.9 mass% or less of bisphenol condensate per 100 mass% of sponge lead, has a median pore size on a volume basis of 0.5 μm or less, and a porosity of 0.22 mL / g or more and 0.4 mL / g or less.

[0007] Patent Document 5 describes a valve-regulated lead-acid battery having a positive electrode plate, a negative electrode plate, and an electrolyte. The negative electrode plate has a negative electrode current collector and a negative electrode material, and the density of the negative electrode material is 2.6 g / cm 3 and a valve regulated lead-acid battery in which the negative electrode material contains an organic shrinkage preventer and the content of sulfur element in the organic shrinkage preventer is greater than 600 μmol / g. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2017-79166 A [Patent Document 2] International Publication No. 2013 / 150754 [Patent Document 3] JP 2013-161606 A [Patent Document 4] JP 2014-123525 A [Patent Document 5] JP 2018-18742 A Summary of the Invention [Problem to be solved by the invention]

[0009] When a carbonaceous material is contained in the negative electrode material, the carbonaceous material flows out into the electrolyte, and the outflow of the carbonaceous material becomes more pronounced as the content of the carbonaceous material in the negative electrode material increases. [Means for solving the problem]

[0010] One aspect of the present invention is a battery comprising a positive electrode plate, a negative electrode plate, and an electrolyte solution, The negative electrode plate includes a negative electrode material, The negative electrode material includes an organic shrinkage preventer and a carbonaceous material, The organic shrink-proofing agent contains a bisarene compound unit and a monocyclic aromatic compound unit having a hydroxy group, The present invention relates to a lead-acid battery, wherein the bisarene compound unit is at least one selected from the group consisting of a bisphenol S compound unit and a bisphenol A compound unit. Effect of the Invention

[0011] In a lead-acid battery, outflow of carbonaceous material from the negative electrode material can be suppressed. [Brief description of the drawings]

[0012] [Figure 1] 1 is a partially cutaway exploded perspective view showing the appearance and internal structure of a lead-acid battery according to one aspect of the present invention. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] A lead-acid battery according to one aspect of the present invention includes a positive electrode plate, a negative electrode plate, and an electrolyte. The negative electrode plate includes a negative electrode material. The negative electrode material includes an organic shrinkage inhibitor and a carbonaceous material. The organic shrinkage inhibitor includes a bisarene compound unit and a monocyclic aromatic compound unit having a hydroxyl group. The bisarene compound unit is at least one selected from the group consisting of a bisphenol S compound unit and a bisphenol A compound unit. Hereinafter, the monocyclic aromatic compound having a hydroxyl group may be referred to as a hydroxymonoarene compound.

[0014] The above-mentioned configuration suppresses the outflow of the carbonaceous material from the negative electrode material to the electrolyte. The organic shrink-proofing agent contains a hydroxymonoarene compound unit and the above-mentioned bisarene compound unit, so that the high shrink-proofing effect of the organic shrink-proofing agent can be maintained. The hydroxymonoarene compound unit facilitates the formation of a planar structure and increases the flexibility of the organic shrink-proofing agent molecule. The organic shrink-proofing agent usually contains many functional groups having negative polarity, and it is considered that the functional groups having negative polarity tend to be unevenly distributed on the surface of the molecule due to the increase in the flexibility of the molecule. The planar structure and the presence of functional groups having negative polarity unevenly distributed on the surface make it easier for the organic shrink-proofing agent to be adsorbed to the components (lead, lead sulfate, carbonaceous material, etc.) contained in the negative electrode material. The above-mentioned organic shrink-proofing agent adsorbed to the components in the negative electrode material is denatured in the electrolyte and functions like a binder. It is considered that the outflow of the carbonaceous material is suppressed by the binding action of such an organic shrink-proofing agent. In contrast, lignin has a three-dimensionally developed polymer structure. Therefore, compared with the above organic shrinkage inhibitors, lignin has a weaker binding effect on the components contained in the negative electrode material, and even if the lignin content is increased, it may be difficult to obtain the effect of suppressing the outflow of the carbonaceous material.

[0015] The lead acid battery may be a valve regulated (sealed) lead acid battery, but is particularly useful as a flooded (vented) lead acid battery in which leakage of carbonaceous material is likely to be a problem.

[0016] Hereinafter, the lead-acid battery according to the embodiment of the present invention will be described in detail with respect to each of its main components, but the present invention is not limited to the following embodiment.

[0017] [Lead acid battery] (Negative plate) A negative electrode plate usually includes a negative electrode current collector in addition to a negative electrode material. The negative electrode material is the portion of the negative electrode plate excluding the negative electrode current collector. Note that a member such as a mat or pasting paper may be attached to the negative electrode plate. Such a member (attaching member) is used integrally with the negative electrode plate, and is therefore included in the negative electrode plate. Also, when the negative electrode plate includes such a member, the negative electrode material is the portion of the negative electrode plate excluding the negative electrode current collector and the attaching member. However, when an attaching member (such as a mat or pasting paper) is attached to the separator, the thickness of the attaching member is included in the thickness of the separator.

[0018] The negative electrode current collector may be formed by casting lead (Pb) or a lead alloy, or may be formed by processing a lead sheet or a lead alloy sheet. Examples of the processing method include expanding and punching. It is preferable to use a lattice-shaped current collector as the negative electrode current collector because it is easy to support the negative electrode material.

[0019] The lead alloy used for the negative electrode current collector may be any of Pb-Sb alloy, Pb-Ca alloy, and Pb-Ca-Sn alloy. These lead or lead alloys may further contain at least one selected from the group consisting of Ba, Ag, Al, Bi, As, Se, Cu, etc. as an additive element. The negative electrode current collector may have a surface layer. The surface layer and the inner layer of the negative electrode current collector may have different compositions. The surface layer may be formed on a part of the negative electrode current collector. The surface layer may be formed on the ear of the negative electrode current collector. The surface layer of the ear may contain Sn or an Sn alloy.

[0020] The negative electrode material includes an organic shrinkage inhibitor (hereinafter sometimes referred to as a first organic shrinkage inhibitor) containing the above-mentioned bisarene compound unit and hydroxymonoarene compound unit, and a carbonaceous material. The negative electrode material usually further includes a negative electrode active material (lead or lead sulfate) that develops capacity by an oxidation-reduction reaction. The negative electrode material may include at least one selected from the group consisting of another organic shrinkage inhibitor (hereinafter sometimes referred to as a second organic shrinkage inhibitor) and another additive. Examples of additives include barium sulfate, fibers (such as resin fibers), and the like, but are not limited to these. The negative electrode active material in a charged state is sponge-like lead, and the unformed negative electrode plate is usually made using lead powder.

[0021] (Organic shrink-proofing agent) The negative electrode material includes an organic shrinkage inhibitor. The organic shrinkage inhibitor refers to an organic compound among compounds that have the function of suppressing the shrinkage of lead, which is the negative electrode active material, when the lead-acid battery is repeatedly charged and discharged. As already described, the negative electrode material includes a first organic shrinkage inhibitor as an essential component among the organic shrinkage inhibitors, and may further include a second organic shrinkage inhibitor as necessary. The first organic shrinkage inhibitor is an organic shrinkage inhibitor that includes at least one bisarene compound unit selected from the group consisting of bisphenol S compound units and bisphenol A compound units, and a monocyclic aromatic compound (hydroxymonoarene compound) unit having a hydroxy group. The second organic shrinkage inhibitor is an organic shrinkage inhibitor other than the first organic shrinkage inhibitor. The organic shrinkage inhibitor may be, for example, an organic shrinkage inhibitor synthesized by a known method, or a commercially available product.

[0022] Examples of the organic shrinkage inhibitors include synthetic organic shrinkage inhibitors. Synthetic organic shrinkage inhibitors used in lead-acid batteries are usually organic condensates (hereinafter simply referred to as condensates). A condensate is a synthetic product that can be obtained by utilizing a condensation reaction. Since lignin is a natural material, it is excluded from the condensates (synthetic organic shrinkage inhibitors), which are synthetic products. The condensate may contain an aromatic compound unit (hereinafter also referred to as an aromatic compound unit). The aromatic compound unit refers to a unit derived from an aromatic compound incorporated in the condensate. In other words, the aromatic compound unit is a residue of an aromatic compound. The condensate may contain one type of aromatic compound unit, or may contain two or more types.

[0023] The condensate may be, for example, a condensate of an aromatic compound with an aldehyde compound. Such a condensate may be synthesized by reacting an aromatic compound with an aldehyde compound. Here, a condensate containing a sulfur element may be obtained by carrying out the reaction of an aromatic compound with an aldehyde compound in the presence of a sulfite, or by using an aromatic compound containing a sulfur element (e.g., bisphenol S) as an aromatic compound. For example, the sulfur element content in the condensate may be adjusted by adjusting at least one of the amount of sulfite and the amount of the aromatic compound containing a sulfur element. This method may be followed when using other raw materials. The aromatic compound to be condensed to obtain the condensate may be one type or two or more types. The aldehyde compound may be an aldehyde (e.g., formaldehyde), or may be a condensate (or polymer) of an aldehyde. Examples of the aldehyde condensate (or polymer) include paraformaldehyde, trioxane, and tetraoxymethylene. The aldehyde compound may be used alone or in combination of two or more types. From the viewpoint of high reactivity with aromatic compounds, formaldehyde is preferred.

[0024] The aromatic compound may have a sulfur-containing group. That is, the condensate may be an organic polymer containing a plurality of aromatic rings in the molecule and containing elemental sulfur as a sulfur-containing group. The sulfur-containing group may be directly bonded to the aromatic ring of the aromatic compound, or may be bonded to the aromatic ring as an alkyl chain having a sulfur-containing group, for example. Among the sulfur-containing groups, a sulfonic acid group or a sulfonyl group, which is a stable form, is preferred. The sulfonic acid group may exist in an acid form or in a salt form such as a Na salt.

[0025] The sulfur-containing group is a functional group with a strong negative polarity. In an electrolyte, such functional groups form stable bonds with water molecules, hydrogen ions, and hydrogen sulfate ions, so that the functional groups tend to be unevenly distributed on the surface of the condensate. Since such functional groups unevenly distributed on the surface have a negative charge, electrostatic repulsion occurs between the associations of the condensate. This limits the association or aggregation of colloidal particles of the condensate, and the colloidal particle size tends to be small. As a result, it is considered that the pore size of the negative electrode material is small and the resistivity of the negative electrode material is likely to decrease. Therefore, when a condensate having a sulfur-containing group is used, a higher shrinkage prevention effect can be secured, and excellent low-temperature HR discharge performance and charge acceptance can be easily obtained.

[0026] Examples of the aromatic rings that aromatic compounds have include benzene rings and naphthalene rings. When an aromatic compound has multiple aromatic rings, the multiple aromatic rings may be linked by direct bonds or linking groups (e.g., alkylene groups (including alkylidene groups), sulfone groups) and the like. Examples of such structures include bisarene structures (biphenyl, bisphenylalkane, bisphenylsulfone, etc.).

[0027] Examples of aromatic compounds include compounds having the above aromatic ring and a functional group (such as a hydroxy group or an amino group). The functional group may be directly bonded to the aromatic ring, or may be bonded as an alkyl chain having a functional group. The hydroxy group also includes a salt of the hydroxy group (-OMe). The amino group also includes a salt of the amino group (a salt with an anion). Examples of Me include alkali metals (Li, K, Na, etc.) and metals of Group 2 of the periodic table (Ca, Mg, etc.). The aromatic compound may have a sulfur-containing group and a substituent other than the above functional group (such as an alkyl group or an alkoxy group) on the aromatic ring.

[0028] The aromatic compound that is the source of the aromatic compound unit may be at least one selected from the group consisting of bisarene compounds and monocyclic aromatic compounds.

[0029] Examples of the bisarene compound include bisarene compounds having a hydroxy group (such as bisphenol compounds and hydroxybiphenyl compounds), and bisarene compounds having an amino group (such as bisarylalkane compounds having an amino group, bisarylsulfone compounds having an amino group, and biphenyl compounds having an amino group). Among these, bisarene compounds having a hydroxy group (particularly, bisphenol compounds) are preferred.

[0030] The bisphenol compound is preferably bisphenol A, bisphenol S, bisphenol F, or the like. For example, the bisphenol compound may contain at least one selected from the group consisting of bisphenol A and bisphenol S. By using bisphenol A or bisphenol S, an excellent shrinkage prevention effect on the negative electrode material can be obtained.

[0031] The bisphenol compound may have a bisphenol skeleton, and the bisphenol skeleton may have a substituent. That is, bisphenol A may have a bisphenol A skeleton, and the skeleton may have a substituent. Bisphenol S may have a bisphenol S skeleton, and the skeleton may have a substituent.

[0032] Preferred monocyclic aromatic compounds include hydroxymonoarene compounds, monocyclic aromatic compounds having an amino group (aminomonoarene compounds), etc. Among these, hydroxymonoarene compounds are preferred.

[0033] Examples of the hydroxymonoarene compound include a hydroxynaphthalene compound and a phenol compound. For example, it is preferable to use a phenolsulfonic acid compound (such as phenolsulfonic acid or a substituted product thereof) which is a phenol compound. The condensate containing the unit of the phenolsulfonic acid compound has a phenolic hydroxy group and a sulfonic acid group. Both the phenolic hydroxy group and the sulfonic acid group are hydrophilic groups with strong polarity that exhibit acidity, and the functional group is negatively charged. Therefore, the condensate containing the unit of the phenolsulfonic acid compound has a high adsorption force to lead and lead sulfate in the negative electrode material. In addition, since the condensate is likely to have a planar structure due to phenolsulfonic acid, the condensate is likely to exist in the vicinity of the carbonaceous material. Therefore, when such a condensate is used, it is easy to obtain high binding properties, and the effect of suppressing the outflow of the carbonaceous material can be further improved. As already mentioned, the phenolic hydroxy group also includes a salt (-OMe) of the phenolic hydroxy group.

[0034] Examples of the aminomonoarene compounds include aminonaphthalene compounds and aniline compounds (such as aminobenzenesulfonic acid and alkylaminobenzenesulfonic acid).

[0035] The organic shrink-proofing agent also includes a lignin compound. In this specification, the lignin compound includes lignin and a lignin derivative. The lignin derivative includes one having a lignin-like three-dimensional structure. The lignin derivative includes, for example, at least one selected from modified lignin, lignin sulfonic acid, modified lignin sulfonic acid, and salts thereof (alkali metal salts (such as sodium salts), magnesium salts, calcium salts, etc.).

[0036] The sulfur element content of the organic shrink-proofing agent other than the lignin compound may be, for example, 2000 μmol / g or more, or 3000 μmol / g or more. When an organic shrink-proofing agent having such a sulfur element content is used, the colloid particle size of the organic shrink-proofing agent is likely to be small, and the structure of the negative electrode material can be kept fine, so that high low-temperature high-rate (HR) discharge performance is likely to be ensured. In addition, when the sulfur element content of the first organic shrink-proofing agent described later is in such a range, in the organic shrink-proofing agent to which flexibility is imparted by the unit of the monocyclic aromatic compound having a hydroxyl group, the functional group containing the sulfur element is likely to be unevenly distributed on the surface of the organic shrink-proofing agent. Therefore, the outflow suppression effect of the carbonaceous material can be further improved.

[0037] The sulfur element content in the organic shrink-proofing agent being X μmol / g means that the sulfur element content per 1 g of the organic shrink-proofing agent is X μmol.

[0038] The upper limit of the sulfur element content of the organic shrink inhibitor other than the lignin compound is not particularly limited, but may be, for example, 9000 μmol / g or less, 8000 μmol / g or less, or 7000 μmol / g or less.

[0039] The organic shrink-proofing agent other than the lignin compound also includes an organic shrink-proofing agent having a sulfur element content of less than 2000 μmol / g. The sulfur element content of such an organic shrink-proofing agent may be 300 μmol / g or more.

[0040] The sulfur element content of the organic shrink inhibitor other than the lignin compound may be, for example, 2000 μmol / g or more (or 3000 μmol / g or more) and 9000 μmol / g or less, 2000 μmol / g or more (or 3000 μmol / g or more) and 8000 μmol / g or less, 2000 μmol / g or more (or 3000 μmol / g or more) and 7000 μmol / g or less, 300 μmol / g or more and 9000 μmol / g or less (or 8000 μmol / g or less), or 300 μmol / g or more and 7000 μmol / g or less (or less than 2000 μmol / g).

[0041] The weight average molecular weight (Mw) of the organic shrink-proofing agent other than the lignin compound is, for example, preferably not less than 7000. The Mw of the organic shrink-proofing agent is, for example, not more than 100,000, and may be not more than 20,000.

[0042] The sulfur element content of the lignin compound is, for example, less than 2000 μmol / g, and may be 1000 μmol / g or less, or 800 μmol / g or less. The lower limit of the sulfur element content of the lignin compound is not particularly limited, but is, for example, 400 μmol / g or more.

[0043] The Mw of the lignin compound is, for example, less than 7000. The Mw of the lignin compound is, for example, 3000 or more.

[0044] In this specification, the Mw of the organic shrink-preventing agent is determined by gel permeation chromatography (GPC). The standard substance used in determining the Mw is sodium polystyrene sulfonate. Mw is measured using the following apparatus under the following conditions. GPC equipment: Build-up GPC system SD-8022 / DP-8020 / AS-8020 / CO-8020 / UV-8020 (Tosoh Corporation) Column: TSKgel G4000SWXL, G2000SWXL (7.8 mm I.D. x 30 cm) (Tosoh Corporation) Detector: UV detector, λ=210nm Eluent: A mixture of 1 mol / L NaCl aqueous solution: acetonitrile (volume ratio = 7:3) Flow rate: 1mL / min. Concentration: 10mg / mL Injection volume: 10μL Standard substance: Sodium polystyrene sulfonate (Mw=275,000, 35,000, 12,500, 7,500, 5,200, 1,680)

[0045] Among the organic shrinkage inhibitors, the first organic shrinkage inhibitor may be, for example, one containing a bisarene compound unit (hereinafter sometimes referred to as the first unit) and the above-mentioned monocyclic aromatic compound unit having a hydroxyl group (hereinafter sometimes referred to as the second unit) (e.g., a condensate). Here, the first unit is at least one selected from the group consisting of a bisphenol S compound unit and a bisphenol A compound unit. The first organic shrinkage inhibitor may further contain another aromatic compound unit (third unit) as necessary.

[0046] By including the first unit in the first organic shrink-proofing agent, a high shrink-proofing effect of the negative electrode material can be ensured. In addition, the first unit has a structure in which the linking group connecting the two aromatic rings protrudes from the aromatic ring plane, compared to the second unit, so that the first organic shrink-proofing agent containing the first unit is less likely to adsorb to lead or lead sulfate. However, even if the first organic shrink-proofing agent contains the first unit, the first organic shrink-proofing agent is more likely to have a planar structure by including the second unit. In organic shrink-proofing agents containing the first unit, the aromatic rings generally tend to interact with each other between π electrons and become rigid. However, in the first organic shrink-proofing agent, the second unit inhibits the π electron interaction of the first unit, so that the flexibility of the molecule can be increased. It is considered that this makes it easier for the functional group having negative polarity contained in the first organic shrink-proofing agent to be unevenly distributed on the molecular surface. Therefore, the high adsorption of the first organic shrink-proofing agent to lead and lead sulfate can be ensured, and the outflow of the carbonaceous material can be suppressed.

[0047] The first unit preferably includes at least a bisphenol S compound unit. The first organic shrinkage inhibitor may include a bisphenol S compound unit and a bisphenol A compound unit as the first unit. The bisphenol S skeleton has a structure in which two benzene rings are linked by a sulfonyl group. The bisphenol A skeleton has a structure in which two benzene rings are linked by a dimethylene group. The sulfonyl group protrudes less from the benzene ring plane than the dimethylene group. Therefore, the bisphenol S compound unit makes it easier for the first organic shrinkage inhibitor to have a planar structure than the bisphenol A compound unit. In addition, due to the presence of the sulfonyl group, the bisphenol S compound unit makes it easier for the first organic shrinkage inhibitor to be negatively charged than the bisphenol A compound unit. Therefore, when a first organic shrinkage inhibitor having at least a bisphenol S compound unit is used as the first unit, the adsorption of the first organic shrinkage inhibitor to lead and lead sulfate is further increased, and it is considered that the effect of suppressing the outflow of carbonaceous materials can be further improved.

[0048] As the second unit, a unit of a monocyclic aromatic compound having a phenolic hydroxy group is preferred. In the condensation product of a monocyclic aromatic compound having a phenolic hydroxy group with an aldehyde compound, the condensation is mainly at least one of the ortho and para positions (particularly the ortho position) with respect to the phenolic hydroxy group. On the other hand, in the condensation product of a monocyclic aromatic compound having an amino group with an aldehyde compound, the condensation is performed via the amino group. Therefore, when a monocyclic aromatic compound having a phenolic hydroxy group is used, the aromatic rings in the organic shrink-proofing agent molecule are less twisted than when a monocyclic aromatic compound having an amino group is used, and it is easier to take a planar structure, which is thought to make it easier to act on lead and lead sulfate.

[0049] Among the above monocyclic aromatic compound units, it is preferable to use a first organic shrinkage inhibitor containing a phenolsulfonic acid compound unit as the second unit. Such a first organic shrinkage inhibitor has a phenolic hydroxy group and a sulfonic acid group. Both the phenolic hydroxy group and the sulfonic acid group have strong negative polarity and high affinity with metals. Therefore, a condensate containing a phenolsulfonic acid compound unit as the second unit has a higher adsorption property to lead and lead sulfate. This makes it easier for the first organic shrinkage inhibitor to exist in the vicinity of the carbonaceous material in the negative electrode material, thereby further enhancing the effect of suppressing the outflow of the carbonaceous material.

[0050] The molar ratio of the second unit to the total amount of the first unit and the second unit is, for example, 10 mol% or more, and may be 20 mol% or more. When the molar ratio is in this range, the first organic shrink-proofing agent is more likely to have a planar structure. The molar ratio of the second unit is, for example, 90 mol% or less, and may be 80 mol% or less.

[0051] The molar ratio of the second unit may be 10 mol % or more (or 20 mol % or more) and 90 mol % or less, or 10 mol % or more (or 20 mol % or more) and 80 mol % or less.

[0052] In the first organic shrink-proofing agent, the total ratio (molar ratio) of the first unit and the second unit to the total amount of the aromatic compound unit is, for example, 90 mol% or more, and may be 95 mol% or more. In addition, the aromatic compound unit may be composed of only the first unit and the second unit.

[0053] The sulfur element content and Mw of the first organic shrink-proofing agent can each be selected from the above ranges.

[0054] The first organic shrink-proofing agent may be used alone or in combination of two or more kinds.

[0055] Among the above organic shrinkage inhibitors, examples of the second organic shrinkage inhibitor include condensates containing units of lignin compounds and bisarene compounds (such as bisphenol compounds) (such as condensates containing units of bisphenol S compounds and units of bisphenol A compounds).

[0056] The second organic shrink-proofing agent may be used alone or in combination of two or more. For example, a second organic shrink-proofing agent other than a lignin compound may be used in combination with a lignin compound.

[0057] When the first organic shrink-proofing agent and the second organic shrink-proofing agent are used in combination, the mass ratio thereof can be selected arbitrarily. Even when the second organic shrink-proofing agent is used in combination, the outflow suppression effect of the carbonaceous material can be obtained according to the mass ratio of the first organic shrink-proofing agent. From the viewpoint of ensuring a higher suppression effect on the outflow of the carbonaceous material, the ratio of the first organic shrink-proofing agent to the entire organic shrink-proofing agent (i.e., the total amount of the first organic shrink-proofing agent and the second organic shrink-proofing agent) is preferably 20 mass% or more, may be 50 mass% or more, or may be 80 mass% or more.

[0058] The content of the organic shrinkage inhibitor in the negative electrode material is 2 For example, the content of the organic shrinkage inhibitor is 1.5 mg or more, and may be 1.7 mg or more. From the viewpoint of obtaining a higher carbonaceous material outflow suppression effect and easily ensuring high low-temperature HR discharge performance, the content of the organic shrinkage inhibitor is preferably more than 1.7 mg, and more preferably 1.8 mg or more or 2 mg or more. The content of the organic shrinkage inhibitor is, for example, 3.8 mg or less, and may be 3.7 mg or less. From the viewpoint of easily ensuring high charge acceptance, the content of the organic shrinkage inhibitor is preferably less than 3.7 mg, and may be 3.6 mg or less, 3.5 mg or less, or 3.4 mg or less. The content of the first organic shrinkage inhibitor in the negative electrode material may be within such a range.

[0059] The content of the organic shrinkage inhibitor in the negative electrode material is 2Per day, 1.5mg or more (1.7mg or more) but not exceeding 3.8mg, 1.5mg or more (1.7mg or more) but not exceeding 3.7mg, 1.5mg or more (1.7mg or more) but not exceeding 3.7mg, 1.5mg or more (1.7mg or more) but not exceeding 3.6mg, 1.5mg or more (1.7mg or more) but not exceeding 3.5mg, 1.5mg or more (1.7mg or more) but not exceeding 3.4mg, more than 1.7mg (or 1.8mg or more) but not exceeding 3.8mg, more than 1.7mg (or 1.8mg or more) but not exceeding 3.7mg The content of the first organic shrink-proofing agent in the negative electrode material may be within such a range.

[0060] The surface area of ​​the negative electrode material is the BET specific surface area (m2) of the negative electrode material determined by the gas adsorption method using nitrogen gas. 2 ·g -1 ) multiplied by the mass (g) of the negative electrode material.

[0061] The surface area of ​​the negative electrode material, the mass of the negative electrode material, and the content of the organic shrinkage preventer in the negative electrode material are each determined for the negative electrode plate of a fully charged lead-acid battery.

[0062] In this specification, the fully charged state of a flooded lead-acid battery is defined by the definition of JIS D 5301:2006. More specifically, the fully charged state is defined as a state in which a lead-acid battery is charged in a water tank at 25°C ± 2°C with a current (A) 0.2 times the value listed as the rated capacity (Ah) until the terminal voltage during charging or the electrolyte density converted to a temperature of 20°C shows a constant value with three significant digits three consecutive times. In addition, in the case of a valve-regulated lead-acid battery, the fully charged state is defined as a state in which a lead-acid battery is charged at a constant current and constant voltage of 2.23 V / cell in an air tank at 25°C ± 2°C with a current (A) 0.2 times the value listed as the rated capacity (Ah), and charging is terminated when the charging current (A) during constant voltage charging becomes 0.005 times the value listed as the rated capacity. The value listed as the rated capacity is in Ah. The unit of the current set based on the value listed as the rated capacity is A.

[0063] A fully charged lead-acid battery refers to a lead-acid battery that has already been chemically prepared and is fully charged. A lead-acid battery may be fully charged immediately after chemical preparation, or after a certain amount of time has passed since chemical preparation (for example, a lead-acid battery that is in use (preferably in the early stages of use) after chemical preparation may be fully charged). An early stage battery refers to a battery that has not been in use for very long and has hardly deteriorated at all.

[0064] (carbonaceous material) Examples of carbonaceous materials include carbon black, graphite, hard carbon, and soft carbon. Examples of carbon black include acetylene black, furnace black, and lamp black. Furnace black also includes Ketjen Black (trade name). Graphite may be any carbonaceous material containing a graphite-type crystal structure, and may be either artificial graphite or natural graphite. The carbonaceous material may be used alone or in combination of two or more.

[0065] In addition, among carbonaceous materials, the 1300 cm -1 More than 1350cm -1 Peaks appearing in the following range (D band) and 1550 cm -1More than 1600cm -1 Intensity ratio I to the peak (G band) appearing in the following range D / I G A carbonaceous material having a σ of 0 or more and 0.9 or less is called graphite. Graphite may be either artificial graphite or natural graphite.

[0066] The carbonaceous material may include a first carbonaceous material having a particle size of 32 μm or more, and may include a second carbonaceous material having a particle size of less than 32 μm. The carbonaceous material may include both the first carbonaceous material and the second carbonaceous material. The first carbonaceous material and the second carbonaceous material are separated and distinguished by a procedure described below.

[0067] The first carbonaceous material may be, for example, at least one selected from the group consisting of graphite, hard carbon, and soft carbon. Among them, the first carbonaceous material preferably contains at least graphite. By using graphite, it is possible to ensure even higher PSOC life performance. The second carbonaceous material preferably contains at least carbon black.

[0068] When the carbonaceous material includes the second carbonaceous material, the proportion of the second carbonaceous material in the entire carbonaceous material is, for example, 10% by mass or more, and may be 40% by mass or more, 50% by mass or more, or 60% by mass or more. When the proportion of the second carbonaceous material is in such a range, it is advantageous in ensuring higher charge acceptance. The proportion of the second carbonaceous material in the entire carbonaceous material is, for example, 100% by mass or less. From the viewpoint of easily ensuring higher low-temperature HR discharge performance, the proportion of the second carbonaceous material may be 90% by mass or less.

[0069] The proportion of the second carbonaceous material in the entire carbonaceous material may be 10% by mass or more (or 40% by mass or more) and 100% by mass or less, 10% by mass or more (or 40% by mass or more) and 90% by mass or less, 50% by mass or more (or 60% by mass or more) and 100% by mass or less, or 50% by mass or more (or 60% by mass or more) and 90% by mass or less.

[0070] The content of the carbonaceous material in the negative electrode material is, for example, 0.1% by mass or more, and may be 0.3% by mass or more. From the viewpoint of easily ensuring higher charge acceptance, it is preferably 0.5% by mass or more or 0.9% by mass or more. On the other hand, when the content of the carbonaceous material is 0.5% by mass or more or 0.9% by mass or more, the outflow of the carbonaceous material becomes significant. In the lead-acid battery according to one aspect of the present invention, even when the content of the carbonaceous material in the negative electrode material is as high as 0.5% by mass or more or 0.9% by mass or more, the outflow of the carbonaceous material can be effectively suppressed by the action of the first organic shrinkage inhibitor. The content of the carbonaceous material is, for example, 5% by mass or less, and may be 3.5% by mass or less.

[0071] The content of the carbonaceous material may be 0.1% by mass or more and 5% by mass or less (or 3.5% by mass or less), 0.3% by mass or more and 5% by mass or less (or 3.5% by mass or less), 0.5% by mass or more and 5% by mass or less (or 3.5% by mass or less), or 0.9% by mass or more and 5% by mass or less (or 3.5% by mass or less).

[0072] (Barium Sulfate) The negative electrode material may contain barium sulfate. The content of barium sulfate in the negative electrode material is, for example, 0.05% by mass or more, and may be 0.10% by mass or more. The content of barium sulfate in the negative electrode material is, for example, 3% by mass or less, and may be 2% by mass or less.

[0073] The content of barium sulfate in the negative electrode material may be from 0.05 to 3% by mass, from 0.05 to 2% by mass, from 0.10 to 3% by mass, or from 0.10 to 2% by mass.

[0074] The density of the negative electrode material is, for example, 3.0 g / cm 3 More than 3.2g / cm 3 From the viewpoint of further enhancing the effect of suppressing the outflow of the carbonaceous material, the density of the negative electrode material may be 3.3 g / cm or more. 3 The density of the negative electrode material is preferably 3.8 g / cm or more. 3 Less than or equal to 3.7 g / cm3 It may be the following. The density of the negative electrode material means the bulk density of the negative electrode material in a fully charged state.

[0075] The density of the negative electrode material is, for example, 3.0 g / cm 3 More than 3.8g / cm 3 or less (or 3.7g / cm 3 below), 3.2g / cm 3 More than 3.8g / cm 3 or less (or 3.7g / cm 3 or less), or 3.3 g / cm 3 More than 3.8g / cm 3 or less (or 3.7g / cm 3 (see below) may also be used.

[0076] (Analysis of the components of negative electrode materials) The following describes a method for analyzing the negative electrode material or its components. Prior to the analysis, the lead-acid battery after chemical formation is fully charged and then disassembled to obtain the negative plate to be analyzed. The obtained negative plate is washed with water to remove sulfuric acid from the negative plate. The washing is performed by pressing a pH test paper against the washed surface of the negative plate until it is confirmed that the color of the test paper does not change. However, the washing time is within 2 hours. The washed negative plate is dried at 60±5°C for about 6 hours in a reduced pressure environment. After drying, if the negative plate contains an attachment material, the attachment material is removed from the negative plate by peeling. Next, the negative electrode material is separated from the negative plate to obtain a sample (hereinafter referred to as sample A), and the mass (M0) of sample A is measured. Sample A is crushed as necessary and subjected to analysis.

[0077] (1) Analysis of organic shrinkage inhibitors (1-1) Qualitative analysis of organic shrinkage inhibitors in negative electrode materials The crushed sample A is immersed in a 1 mol / L aqueous solution of sodium hydroxide (NaOH) to extract the organic shrink-preventing agent. If the extract contains multiple organic shrink-preventing agents, each organic shrink-preventing agent is then separated from the extract. For each of the isolated materials containing each organic shrink-preventing agent, insoluble components are removed by filtration, and the resulting solution is desalted, concentrated, and dried. Desalting is performed using a desalting column, or by passing the solution through an ion exchange membrane, or by placing the solution in a dialysis tube and immersing it in distilled water. This is dried to obtain a powder sample of the organic shrink-preventing agent (hereinafter referred to as sample B).

[0078] The type of organic shrink-preventing agent is identified by combining information obtained from the infrared spectrum measured using sample B of the organic shrink-preventing agent thus obtained, the ultraviolet-visible absorption spectrum measured with an ultraviolet-visible spectrometer after diluting sample B with distilled water or the like, or the NMR spectrum of a solution obtained by dissolving sample B in a specified solvent such as heavy water.

[0079] When the extract contains a plurality of organic shrink-preventing agents, they are separated as follows.

[0080] First, the extract is measured by at least one of infrared spectroscopy, NMR, and GC-MS to determine whether it contains multiple organic shrink-preventing agents. Next, the extract is subjected to GPC analysis to measure the molecular weight distribution. If the multiple organic shrink-preventing agents can be separated by molecular weight, the organic shrink-preventing agents are separated by column chromatography based on the difference in molecular weight.

[0081] The organic shrink-preventing agent has different solubilities if at least one of the type and amount of functional groups is different. When it is difficult to separate the organic shrink-preventing agent due to the difference in molecular weight, such a difference in solubility is utilized to separate one of the organic shrink-preventing agents by a precipitation separation method. For example, when two types of organic shrink-preventing agents are contained, one of the organic shrink-preventing agents is flocculated and separated by dropping an aqueous sulfuric acid solution into a mixture in which the above extract is dissolved in an aqueous NaOH solution to adjust the pH of the mixture. When separation by flocculation is difficult, the first organic shrink-preventing agent is separated by ion exchange chromatography or affinity chromatography using at least one of the difference in the type and amount of functional groups. The separated material is dissolved again in an aqueous NaOH solution, and the insoluble components are removed by filtration as described above. The remaining solution after separation of one of the organic shrink-preventing agents is concentrated. The obtained concentrate contains the other organic shrink-preventing agent, and the insoluble components are removed by filtration from this concentrate as described above.

[0082] (1-2) Quantitative determination of organic shrinkage inhibitor content in negative electrode material As in the above (1-1), a solution is obtained by removing insoluble components from each of the separated products containing the organic shrinkage inhibitor by filtration. The ultraviolet-visible absorption spectrum of each of the obtained solutions is measured. The content of each organic shrinkage inhibitor in the negative electrode material is determined using the intensity of the peak characteristic of each organic shrinkage inhibitor and a calibration curve prepared in advance.

[0083] In addition, when a lead-acid battery with an unknown content of organic shrink-proofing agent is obtained and the content of the organic shrink-proofing agent is measured, the structural formula of the organic shrink-proofing agent cannot be precisely specified, so the same organic shrink-proofing agent cannot be used for the calibration curve. In this case, a calibration curve is created using the organic shrink-proofing agent extracted from the negative electrode of the battery and a separately available organic polymer that shows similar shapes in the ultraviolet-visible absorption spectrum, infrared spectroscopy spectrum, and NMR spectrum, and the content of the organic shrink-proofing agent is measured using the ultraviolet-visible absorption spectrum.

[0084] (1-3) Sulfur content in organic shrinkage inhibitors As in (1-1) above, after obtaining sample B of the organic shrink-proofing agent, the sulfur element in 0.1 g of the organic shrink-proofing agent is converted to sulfuric acid by the oxygen combustion flask method. At this time, sample B is burned in a flask containing an adsorption solution to obtain an eluate in which sulfate ions are dissolved in the adsorption solution. Next, the sulfur element content (C0) in 0.1 g of the organic shrink-proofing agent is obtained by titrating the eluate with barium perchlorate using thorin as an indicator. Next, C0 is multiplied by 10 to calculate the sulfur element content (μmol / g) in the organic shrink-proofing agent per 1 g.

[0085] (2) Analysis of carbonaceous materials (2-1) Separation and quantification of carbonaceous materials A predetermined amount of the crushed sample A is taken and the mass is measured. 30 mL of nitric acid solution with a concentration of 60% by mass per 5 g of sample A is added to this sample A and heated at 70°C ± 5°C. 10 g of disodium ethylenediaminetetraacetate, 30 mL of ammonia water with a concentration of 28% by mass, and 100 mL of water are added to the resulting mixture with respect to 5 g of sample A, and heating is continued to dissolve the soluble matter. In this way, the sample A is pretreated. The dispersion obtained by the pretreatment is filtered using a membrane filter (0.1 μm mesh) to recover the solid matter. The recovered sample is sieved with a 500 μm mesh to remove large-sized components (such as reinforcing materials), and the components that passed through the sieve are recovered as carbonaceous materials.

[0086] The content (Cc) of the carbonaceous material in the negative electrode material is determined by measuring the mass of each carbonaceous material separated by the above procedure and calculating the ratio (mass%) of the total mass to the measured mass of sample A.

[0087] When the first carbonaceous material and the second carbonaceous material are separated, the separation is carried out in the following procedure. When the recovered carbonaceous material is wet sieved using a sieve with 32 μm mesh, the material that does not pass through the sieve and remains on the sieve is called the first carbonaceous material, and the material that passes through the sieve is called the second carbonaceous material. In other words, the particle size of each carbonaceous material is based on the size of the sieve mesh. For information on wet sieving, see JIS Z8815:1994.

[0088] Specifically, the carbonaceous material is placed on a sieve with 32 μm mesh, and sieved by gently shaking the sieve for 5 minutes while spraying ion-exchanged water. The first carbonaceous material remaining on the sieve is collected from the sieve by pouring ion-exchanged water over it, and separated from the ion-exchanged water by filtration. The second carbonaceous material that passed through the sieve is collected by filtration using a nitrocellulose membrane filter (0.1 μm mesh). The collected first and second carbonaceous materials are each dried at a temperature of 100°C ± 5°C for 2 hours. As the sieve with 32 μm mesh, one having a sieve mesh with a nominal mesh size of 32 μm as specified in JIS Z 8801-1:2006 is used.

[0089] The proportion of the second carbonaceous material in the entire carbonaceous material is determined by calculating the ratio (mass %) of the measured mass of the second carbonaceous material to the mass of the carbonaceous material (the sum of the masses of each carbonaceous material).

[0090] (3) Surface area of ​​the negative electrode material The surface area of ​​the negative electrode material is determined by multiplying the BET specific surface area of ​​the negative electrode material by the mass of the negative electrode material used in determining the carbonaceous material content Cc (i.e., the mass (g) of the pulverized sample A measured in (2-1) above). The BET specific surface area of ​​the negative electrode material is determined by the BET equation through a gas adsorption method using sample A. Sample A is pretreated by heating in a nitrogen flow at a temperature of 150°C ± 5°C for 1 hour. The BET specific surface area of ​​the pretreated sample A is determined using the following apparatus under the following conditions, and this is taken as the BET specific surface area of ​​the negative electrode material. Measurement equipment: Micromeritics TriStar3000 Adsorption gas: Nitrogen gas with a purity of 99.99% or higher Adsorption temperature: liquid nitrogen boiling point (77K) Calculation method for BET specific surface area: Complies with 7.2 of JIS Z 8830:2013

[0091] (4) Determination of barium sulfate 50 ml of 20% by mass nitric acid is added to 10 g of the crushed sample A, and the mixture is heated for about 20 minutes to dissolve the lead components as lead nitrate. Next, the solution containing lead nitrate is filtered to separate the carbonaceous material, barium sulfate, and other solids.

[0092] The obtained solid content is dispersed in water to prepare a dispersion liquid, and then components other than the carbonaceous material and barium sulfate (e.g., reinforcing material) are removed from the dispersion liquid using a sieve. Next, the dispersion liquid is subjected to suction filtration using a membrane filter whose mass has been measured in advance, and the membrane filter together with the filtered sample is dried in a dryer at 110°C ± 5°C. The obtained sample is a mixed sample of the carbonaceous material and barium sulfate (hereinafter referred to as sample C). The mass of sample C is measured by subtracting the mass of the membrane filter from the total mass of sample C after drying and the membrane filter. Then, the dried sample C is placed in a crucible together with the membrane filter and incinerated at 700°C or higher. The remaining residue is barium oxide. The mass of barium oxide is converted to the mass of barium sulfate to determine the mass of barium sulfate.

[0093] (Measurement of density of negative electrode material) The density of the negative electrode material is measured as follows. A specified amount of sample A is taken and its mass is measured. This sample A is placed in a measurement container, which is then evacuated under reduced pressure, and filled with mercury at a pressure of 0.5 psia to 0.55 psia (≒ 3.45 kPa to 3.79 kPa). The bulk volume of sample A is measured, and the bulk density of the negative electrode material is calculated by dividing the measured mass of sample A by the bulk volume. The bulk volume is the volume of the measurement container minus the volume of the mercury injected.

[0094] The density of the negative electrode material is measured using an automatic porosimeter (Autopore IV9505) manufactured by Shimadzu Corporation.

[0095] (others) The negative electrode plate can be formed by applying or filling a negative electrode paste onto a negative electrode current collector, aging and drying to prepare an unformed negative electrode plate, and then chemically forming the unformed negative electrode plate. The negative electrode paste is prepared by adding water and sulfuric acid to lead powder, an organic shrinkage inhibitor, and various additives as necessary, and kneading them. When aging, it is preferable to age the unformed negative electrode plate at a temperature higher than room temperature and at a high humidity.

[0096] The formation can be carried out by immersing the plate group including the unformed negative plate in an electrolyte containing sulfuric acid in a lead-acid battery container and charging the plate group. However, the formation may be carried out before assembling the lead-acid battery or the plate group. The formation produces spongy lead.

[0097] (Positive plate) The positive electrode plate of a lead-acid battery usually includes a positive electrode current collector and a positive electrode material. The positive electrode material is held by the positive electrode current collector. The positive electrode plate of a lead-acid battery can be classified into a paste type, a clad type, and the like. Either the paste type or the clad type positive electrode plate may be used.

[0098] The positive electrode current collector may be formed by casting lead (Pb) or a lead alloy, or may be formed by processing a lead sheet or a lead alloy sheet. Examples of the processing method include expanding and punching. It is preferable to use a lattice-shaped current collector as the positive electrode current collector because it is easy to support the positive electrode material.

[0099] As the lead alloy used for the positive electrode current collector, in terms of corrosion resistance and mechanical strength, Pb-Sb alloy, Pb-Ca alloy, Pb-Ca-Sn alloy are preferable. The positive electrode current collector may have a surface layer. The surface layer and the inner layer of the positive electrode current collector may have different compositions. The surface layer may be formed on a part of the positive electrode current collector. The surface layer may be formed only on the lattice part, the edge part, or the frame part of the positive electrode current collector.

[0100] In a paste-type positive plate, the positive electrode material is the portion of the positive plate excluding the positive current collector. A member such as a mat or pasting paper may be attached to the positive plate. Such members (attaching members) are used integrally with the positive plate and are therefore considered to be included in the positive plate. In addition, when the positive plate includes an attaching member (mat, pasting paper, etc.), in a paste-type positive plate, the positive electrode material is the portion of the positive plate excluding the positive current collector and the attaching member.

[0101] The positive electrode material contained in the positive electrode plate contains a positive electrode active material (lead dioxide or lead sulfate) that develops capacity through an oxidation-reduction reaction. The positive electrode material may contain other additives as necessary.

[0102] An unformed paste-type positive electrode plate is obtained by filling a positive electrode current collector with a positive electrode paste, aging it, and drying it. The positive electrode paste is prepared by kneading lead powder, an additive, water, and sulfuric acid.

[0103] A positive plate is obtained by chemically forming an unformed positive plate. Chemical formation can be performed by immersing an electrode plate group including an unformed positive plate in an electrolyte containing sulfuric acid in a battery container of a lead-acid battery and charging the electrode plate group. However, chemical formation may be performed before assembling the lead-acid battery or the electrode plate group.

[0104] (Separator) A separator can be disposed between the negative electrode plate and the positive electrode plate. For example, at least one selected from a nonwoven fabric and a microporous membrane is used as the separator. The thickness of the separator interposed between the negative electrode plate and the positive electrode plate may be selected according to the inter-electrode distance. The number of separators may be selected according to the number of inter-electrode spaces.

[0105] A nonwoven fabric is a mat in which fibers are intertwined without being woven, and is mainly composed of fibers. For example, 60% or more by mass of the nonwoven fabric is made of fibers. As the fibers, glass fibers, polymer fibers (polyolefin fibers, acrylic fibers, polyester fibers (polyethylene terephthalate fibers, etc.), pulp fibers, etc.) can be used. Among them, glass fibers are preferable. The nonwoven fabric may contain components other than fibers (for example, acid-resistant inorganic powder, polymers as binders).

[0106] On the other hand, a microporous membrane is a porous sheet mainly composed of components other than fiber components, and can be obtained, for example, by extruding a composition containing a pore-forming agent (such as at least one of a polymer powder and an oil) into a sheet, and then removing the pore-forming agent to form pores. The microporous membrane is preferably made of an acid-resistant material, and is preferably made mainly of a polymer component. The polymer component is preferably polyolefin (such as polyethylene or polypropylene).

[0107] The separator may be, for example, composed of only a nonwoven fabric or only a microporous membrane. Furthermore, the separator may be, as necessary, a laminate of a nonwoven fabric and a microporous membrane, a laminate of different or the same materials, or a laminate of different or the same materials with recesses and projections interlocked.

[0108] The separator may be in a sheet shape or may be formed in a bag shape. A sheet-shaped separator may be sandwiched between the positive electrode plate and the negative electrode plate. Also, the electrode plate may be sandwiched between a folded sheet-shaped separator. In this case, the positive electrode plate sandwiched between the folded sheet-shaped separator and the negative electrode plate sandwiched between the folded sheet-shaped separator may be stacked, or one of the positive electrode plate and the negative electrode plate may be sandwiched between the folded sheet-shaped separator and stacked with the other electrode plate. Also, the sheet-shaped separator may be folded into a bellows shape, and the positive electrode plate and the negative electrode plate may be sandwiched between the bellows-shaped separator so that the separator is interposed between them. When a separator folded like an accordion is used, the separator may be arranged so that the folded portion is along the horizontal direction of the lead-acid battery (for example, so that the folded portion is parallel to the horizontal direction) or along the vertical direction (for example, so that the folded portion is parallel to the vertical direction). In a separator folded like an accordion, recesses are formed alternately on both main surfaces of the separator. Since the upper portions of the positive and negative plates usually have lugs, when the separator is arranged so that the folded portion is along the horizontal direction of the lead-acid battery, the positive and negative plates are arranged only in the recesses on one main surface side of the separator (that is, a double separator is interposed between the adjacent positive and negative plates). When the separator is arranged so that the folded portion is aligned with the vertical direction of the lead-acid battery, the positive electrode plate can be accommodated in the recess on one main surface side, and the negative electrode plate can be accommodated in the recess on the other main surface side (that is, a single layer of separator can be interposed between adjacent positive and negative electrode plates.) When a pouch-shaped separator is used, the pouch-shaped separator may accommodate either the positive or negative electrode plate.

[0109] In this specification, the up-down direction of the electrode plate is defined by assuming that the side on which the lugs are provided is the upper side and the opposite side to the lugs is the lower side. The up-down direction of the electrode plate may be the same as or different from the up-down direction of the lead-acid battery in the vertical direction. In other words, the lead-acid battery may be placed either vertically or horizontally.

[0110] (electrolyte) The electrolyte is an aqueous solution containing sulfuric acid, and may be gelled as necessary. The electrolyte may contain at least one selected from the group consisting of cations (e.g., metal cations) and anions (e.g., anions other than sulfate anions (e.g., phosphate ions)) as necessary. Examples of metal cations include at least one selected from the group consisting of sodium ions, lithium ions, magnesium ions, and aluminum ions.

[0111] The specific gravity of the electrolyte in a fully charged lead-acid battery at 20° C. is, for example, 1.20 or more, and may be 1.25 or more. The specific gravity of the electrolyte at 20° C. is 1.35 or less, and preferably 1.32 or less.

[0112] The specific gravity of the electrolyte in a fully charged lead-acid battery at 20° C. may be 1.20 or more and 1.35 or less, 1.20 or more and 1.32 or less, 1.25 or more and 1.35 or less, or 1.25 or more and 1.32 or less.

[0113] The lead-acid battery can be obtained by a manufacturing method including a step of assembling the lead-acid battery by housing a positive electrode plate, a negative electrode plate, and an electrolyte in a battery case. In the step of assembling the lead-acid battery, the separator is usually disposed between the positive electrode plate and the negative electrode plate. The step of assembling the lead-acid battery may include a step of chemically forming at least one of the positive electrode plate and the negative electrode plate, if necessary, after the step of housing the positive electrode plate, the negative electrode plate, and the electrolyte in the battery case. The positive electrode plate, the negative electrode plate, the electrolyte, and the separator are each prepared before being housed in the battery case.

[0114] FIG. 1 shows an external appearance of an example of a lead-acid battery according to one embodiment of the present invention. The lead-acid battery 1 includes a battery case 12 that contains a plate group 11 and an electrolyte (not shown). The battery case 12 is divided into a plurality of cell chambers 14 by partition walls 13. Each cell chamber 14 contains one plate group 11. The opening of the battery case 12 is closed by a lid 15 that has a negative electrode terminal 16 and a positive electrode terminal 17. The lid 15 is provided with a vent plug 18 for each cell chamber. When refilling with water, the vent plug 18 is removed and refilling liquid is added. The vent plug 18 may have a function of discharging gas generated in the cell chamber 14 to the outside of the battery.

[0115] Each electrode plate group 11 is formed by stacking a plurality of negative electrode plates 2 and positive electrode plates 3 with a separator 4 interposed therebetween. Here, a pouch-shaped separator 4 that accommodates the negative electrode plates 2 is shown, but the shape of the separator is not particularly limited. In a cell chamber 14 located at one end of the battery case 12, a negative electrode shelf portion 6 that connects a plurality of negative electrode plates 2 in parallel is connected to a through connector 8, and a positive electrode shelf portion 5 that connects a plurality of positive electrode plates 3 in parallel is connected to a positive electrode column 7. The positive electrode column 7 is connected to a positive electrode terminal 17 outside the lid 15. In a cell chamber 14 located at the other end of the battery case 12, a negative electrode column 9 is connected to the negative electrode shelf portion 6, and a through connector 8 is connected to the positive electrode shelf portion 5. The negative electrode column 9 is connected to a negative electrode terminal 16 outside the lid 15. Each through connector 8 passes through a through hole provided in the partition wall 13 to connect the electrode plate groups 11 of adjacent cell chambers 14 in series.

[0116] The positive electrode shelf 5 is formed by welding the lugs provided on the upper part of each positive electrode plate 3 together by a cast-on-strap method or a burning method. The negative electrode shelf 6 is also formed by welding the lugs provided on the upper part of each negative electrode plate 2 together in the same manner as the positive electrode shelf 5.

[0117] The lid 15 of the lead-acid battery has a single structure (single lid), but is not limited to the illustrated example. The lid 15 may have a double structure including, for example, an inner lid and an outer lid (or a top lid). The lid having a double structure may have a reflux structure between the inner lid and the outer lid for returning the electrolyte to the inside of the battery (inside the inner lid) from a reflux port provided in the inner lid.

[0118] The leakage of carbonaceous material into the electrolyte in a lead-acid battery is evaluated as follows. After fully charging, all the electrolyte is removed from one cell of the lead-acid battery, and the carbonaceous material contained in the electrolyte is recovered by filtration. At this time, the carbonaceous material adhering to the separator is also washed with water, and recovered by filtration together with the carbonaceous material contained in the electrolyte. The recovered carbonaceous material is washed with water and dried, and the mass (m e The content Cc (mass%) of the carbonaceous material obtained by the above procedure is multiplied by the mass M0 of the sample A, and the result is divided by 100 to obtain the mass m n Calculate the mass of the carbonaceous material in the electrolyte m e is the mass of the carbonaceous material m n By dividing by m e / m n m e / m n Based on the ratio, the outflow of the carbonaceous material into the electrolyte is evaluated. e / m n A lower ratio means less carbonaceous material is lost.

[0119] m e / m n The ratio is, for example, 5.0 x 10 -2 is less than or equal to 3.0 x 10 -2 or less than 2.0×10 -2 By using the first organic shrink-proofing agent, such m e / m n Therefore, the outflow of the carbonaceous material into the electrolyte can be suppressed to a comparatively low level.

[0120] A negative electrode plate for a lead-acid battery and a lead-acid battery according to one aspect of the present invention will be described below.

[0121] (1) A battery comprising a positive electrode plate, a negative electrode plate, and an electrolyte; The negative electrode plate includes a negative electrode material, The negative electrode material includes an organic shrinkage preventer (first organic shrinkage preventer) and a carbonaceous material, The organic shrink-proofing agent (first organic shrink-proofing agent) includes a bisarene compound unit (first unit) and a monocyclic aromatic compound unit having a hydroxy group (second unit), A lead-acid battery, wherein the bisarene compound unit is at least one selected from the group consisting of a bisphenol S compound unit and a bisphenol A compound unit.

[0122] (2) In the above (1), the sulfur element content of the first organic shrink-proofing agent may be 300 μmol / g or more, 2000 μmol / g or more, or 3000 μmol / g or more.

[0123] (3) In the above (1) or (2), the sulfur element content of the first organic shrink-proofing agent may be 9000 μmol / g or less, 8000 μmol / g or less, or 7000 μmol / g or less.

[0124] (4) In any one of the above (1) to (3), the first organic shrink-preventing agent may have a weight average molecular weight (Mw) of 7,000 or more.

[0125] (5) In the above (1) or (2), the first organic shrink-preventing agent may have a sulfur element content of less than 2000 μmol / g.

[0126] (6) In the above (5), the first organic shrink-proofing agent may have a sulfur element content of 300 μmol / g or more.

[0127] (7) In any one of the above (1) to (6), the weight average molecular weight (Mw) of the first organic shrink-preventing agent may be 100,000 or less, or 20,000 or less.

[0128] (8) In any one of the above (1) to (7), the bisarene compound unit (first unit) may include at least a bisphenol S compound unit.

[0129] (9) In any one of the above (1) to (8), the unit of the monocyclic aromatic compound having a hydroxy group (second unit) may be a unit of a phenolsulfonic acid compound.

[0130] (10) In any one of the above (1) to (9), the molar ratio of the second units to the total amount of the first units and the second units may be 10 mol % or more, or 20 mol % or more.

[0131] (11) In any one of the above (1) to (10), the molar ratio of the second units to the total amount of the first units and the second units may be 90 mol % or less, or 80 mol % or less.

[0132] (12) In any one of the above (1) to (11), the total ratio (molar ratio) of the first unit and the second unit to the total amount of aromatic compound units contained in the first organic shrinkage inhibitor may be 90 mol % or more, or 95 mol % or more.

[0133] (13) In any one of the above (1) to (12), the ratio of the first organic shrink-preventing agent to the total organic shrink-preventing agent contained in the negative electrode material may be 20 mass % or more, 50 mass % or more, or 80 mass % or more.

[0134] (14) In any one of the above (1) to (13), the content of the organic shrink-preventing agent (or the first organic shrink-preventing agent) contained in the negative electrode material is 1 / m2 of the surface area of ​​the negative electrode material. 2 It may be 1.5 mg or more, 1.7 mg or more, more than 1.7 mg, 1.8 mg or more, or 2 mg or more per unit time.

[0135] (15) In any one of the above (1) to (14), the content of the organic shrink-preventing agent (or the first organic shrink-preventing agent) contained in the negative electrode material is 1 / m2 of the surface area of ​​the negative electrode material. 2per unit area, it may be 3.8 mg or less, 3.7 mg or less, less than 3.7 mg, 3.6 mg or less, 3.5 mg or less, or 3.4 mg or less.

[0136] (16) In any one of the above (1) to (15), the carbonaceous material may include at least one of a first carbonaceous material having a particle diameter of 32 μm or more and a second carbonaceous material having a particle diameter of less than 32 μm.

[0137] (17) In the above (16), the proportion of the second carbonaceous material in the entire carbonaceous material may be 10 mass % or more, 40 mass % or more, 50 mass % or more, or 60 mass % or more.

[0138] (18) In the above (16) or (17), the proportion of the second carbonaceous material in the entire carbonaceous material may be 100 mass % or less, or 90 mass % or less.

[0139] (19) In any one of the above (1) to (18), the content of the carbonaceous material in the negative electrode material may be 0.1 mass % or more, 0.3 mass % or more, 0.5 mass % or more, or 0.9 mass % or more.

[0140] (20) In any one of the above (1) to (19), the content of the carbonaceous material in the negative electrode material may be 5 mass % or less, or 3.5 mass % or less.

[0141] (21) In any one of the above (1) to (20), the negative electrode material may contain barium sulfate.

[0142] (22) In the above (21), the content of the barium sulfate in the negative electrode material may be 0.05% by mass or more, or 0.10% by mass or more.

[0143] (23) In the above (21) or (22), the content of the barium sulfate in the negative electrode material may be 3 mass % or less, or 2 mass % or less.

[0144] (24) In any one of the above (1) to (23), the density of the negative electrode material is 3.0 g / cm 3 More than 3.2g / cm 3 or more than 3.3g / cm 3 It may be more than that.

[0145] (25) In any one of the above (1) to (24), the density of the negative electrode material is 3.8 g / cm 3 or less than 3.7g / cm 3 It may be the following.

[0146] (26) In any one of the above (1) to (25), the specific gravity of the electrolyte in the lead-acid battery in a fully charged state at 20° C. may be 1.20 or more, or 1.25 or more.

[0147] (27) In any one of the above (1) to (26), the specific gravity of the electrolyte in the lead-acid battery in a fully charged state at 20° C. may be 1.35 or less, or 1.32 or less.

[0148] [Example] The present invention will be specifically described below based on examples and comparative examples, but the present invention is not limited to the following examples.

[0149] Lead-acid batteries E1 to E10 and R1 to R6 (1) Preparation of lead-acid batteries (a) Preparation of the negative electrode plate The raw material lead powder, barium sulfate, the second carbonaceous material (acetylene black), an organic shrinkage inhibitor, and an appropriate amount of sulfuric acid aqueous solution are mixed to obtain a negative electrode paste. At this time, each component is mixed so that the content of the organic shrinkage inhibitor and the content of the carbonaceous material in the negative electrode material obtained by the above-mentioned procedure are the values ​​shown in Table 1. In addition, the concentration and amount of the sulfuric acid aqueous solution are adjusted so that the density of the negative electrode material obtained by the above-mentioned procedure for a lead-acid battery fully charged after formation is the value shown in Table 1. The negative electrode paste is filled into the mesh of an expanded grid made of a Pb-Ca-Sn alloy, and then aged and dried to obtain an unformed negative electrode plate.

[0150] The organic shrink-preventing agents used are those shown in Table 1. The organic shrink-preventing agents shown in Table 1 are as follows. e1 (first organic shrinkage inhibitor): Formaldehyde condensate of bisphenol S and phenolsulfonic acid (=2:8 (molar ratio)) (sulfur element content: 5000 μmol / g, Mw: 8000) e2 (first organic shrinkage inhibitor): Formaldehyde condensate of bisphenol S and phenolsulfonic acid (=8:2 (molar ratio)) (sulfur element content: 4000 μmol / g, Mw: 8000) e3 (first organic shrinkage inhibitor): Formaldehyde condensate of bisphenol A and phenolsulfonic acid (=8:2 (molar ratio)) (sulfur element content: 900 μmol / g, Mw: 8000) e4 (second organic shrinkage inhibitor): sodium lignosulfonate (sulfur element content: 600 μmol / g, Mw: 5500) e5 (second organic shrinkage inhibitor): A condensation product of bisphenol S and formaldehyde in the presence of sodium sulfite (sulfur element content: 5000 μmol / g, Mw: 8000)

[0151] (b) Preparation of the positive electrode plate The raw lead powder is mixed with an aqueous sulfuric acid solution to obtain a positive electrode paste, which is then filled into the mesh of an expanded lattice made of a Pb-Ca-Sn alloy, aged and dried to obtain an unformed positive electrode plate.

[0152] (c) Preparation of test battery The negative electrode plate is housed in a pouch-shaped separator made of a microporous polyethylene film. One negative electrode plate is sandwiched between two positive electrodes to form an electrode assembly.

[0153] The plate group is placed in a polypropylene container together with the electrolyte to assemble the lead-acid battery. The assembled battery is then chemically treated to complete the flooded lead-acid battery. The output of the lead-acid battery is 2V, and the rated 5-hour rate capacity is 5Ah. The specific gravity of the electrolyte after chemical treatment is 1.28. The negative electrode material after chemical treatment contains 0.5% by mass of barium sulfate.

[0154] (2) Evaluation (a) Leakage of carbonaceous material into the electrolyte After fully charging the lead-acid battery, the leakage of carbon material into the electrolyte was measured using the procedure described above. e / m n Evaluated by ratio.

[0155] (b) Low temperature HR discharge performance After fully charging, the lead-acid battery is discharged at a discharge current (A) that is five times the value listed as the rated capacity (Ah) at -15°C ±0.3°C until the terminal voltage reaches 1V / cell, and the discharge time (discharge duration) (s) at this point is calculated. The low-temperature HR discharge performance is evaluated as the ratio of the discharge duration to the discharge duration of lead-acid battery R1, which is set at 100. The longer the discharge duration, the better the low-temperature HR discharge performance.

[0156] (c) Charge acceptance Under the following conditions, a fully charged lead-acid battery is discharged to a depth of discharge (DOD) of 10%, and then the discharged lead-acid battery is charged. Charge acceptance is calculated by measuring the amount of electricity for 10 seconds after charging begins. Charge acceptance is evaluated as a ratio when the amount of electricity of lead-acid battery R1 is set to 100. Discharge (DOD adjustment): 0.2 times the current value (A) of the rated capacity (Ah), 30 minutes Closed: 24 hours Charging (Charging Acceptance): Constant voltage (2.4V / cell, maximum current 16.67A), 10 seconds Temperature: 25℃±0.3℃

[0157] The results are shown in Table 1.

[0158] [Table 1]

[0159] As shown in Table 1, when the first organic shrink-proofing agent is used as the organic shrink-proofing agent, the outflow of the carbonaceous material is suppressed more than when only the second organic shrink-proofing agent is used (comparison between lead-acid batteries E1 to E3 and R1 to R3, and comparison between lead-acid batteries E4 to E10 and R4 and R6). In the case of the second organic shrink-proofing agent, even if the content in the negative electrode material is increased, the effect of suppressing the outflow of the carbonaceous material is low (comparison between lead-acid batteries E4 to E10 and R6).

[0160] Furthermore, when the content of the carbonaceous material in the negative electrode material is 0.5% by mass or more (particularly, 0.9% by mass or more), the outflow suppression effect of the carbonaceous material by using the first organic shrinkage preventer is more pronounced than when the content is less than 0.5% by mass (or less than 0.9% by mass).

[0161] From the viewpoint of ensuring higher low-temperature HR discharge performance, the content of the organic shrinkage inhibitor is set to 1 m2 of the surface area of ​​the negative electrode material. 2 From the viewpoint of ensuring higher charge acceptance, the content of the organic shrinkage inhibitor is preferably more than 1.7 mg (for example, 1.8 mg or more) per m of the surface area of ​​the negative electrode material, and more preferably 2.0 mg or more. 2 Preferably, the amount is less than 3.7 mg (e.g., 3.5 mg or less), and more preferably 3.4 mg or less.

[0162] From the viewpoint of further enhancing the effect of suppressing the outflow of carbonaceous materials, the density of the negative electrode material is set to 3.3 g / cm 3 The following is preferred:

[0163] Lead-acid batteries E11 and E12 Instead of acetylene black (CB), a carbonaceous material shown in Table 2 is used. The components are mixed so that the content of the carbonaceous material and the content of the organic shrinkage inhibitor obtained by the above-mentioned procedure are the values ​​shown in Table 2 to prepare a negative electrode paste. In addition, for a lead-acid battery fully charged after chemical formation, the concentration and amount of the sulfuric acid aqueous solution are adjusted so that the density of the negative electrode material obtained by the above-mentioned procedure is the value shown in Table 2. Other than these, lead-acid batteries E11 and E12 are produced and evaluated in the same manner as lead-acid battery E4.

[0164] In Table 2, FG is artificial graphite. The results are shown in Table 2. Table 2 also shows the results for the lead-acid battery E4.

[0165] [Table 2]

[0166] As shown in Table 2, even when artificial graphite (first carbonaceous material) is used as the carbonaceous material, the outflow amount of the carbonaceous material can be suppressed. From the viewpoint of ensuring higher low-temperature HR discharge performance, it is preferable to use the first carbonaceous material. Also, from the viewpoint of ensuring higher charge acceptance, it is preferable to use carbon black (second carbonaceous material). [Industrial Applicability]

[0167] The lead-acid battery according to one aspect of the present invention can be suitably used, for example, as a starting power source for vehicles (such as automobiles and motorcycles) and as a power source for industrial power storage devices (such as electric vehicles (such as forklifts)). Note that these uses are merely examples and the use is not limited to these uses. [Explanation of symbols]

[0168] 1:Lead acid battery 2: Negative plate 3: Positive plate 4: Separator 5: Positive electrode shelf 6: Negative electrode shelf 7: Positive pole 8: Through connector 9: Negative pole 11: Plate group 12:Battery container 13: Bulkhead 14: Cell Room 15: Lid 16: Negative terminal 17: Positive terminal 18: Liquid outlet plug

Claims

1. The battery includes a positive electrode plate, a negative electrode plate, and an electrolyte solution. The negative electrode plate includes a negative electrode material, The negative electrode material includes an organic shrinkage preventer and a carbonaceous material, The organic shrinkage inhibitor includes a first organic shrinkage inhibitor, The first organic shrink-proofing agent includes a first unit which is a unit of a bisarene compound and a second unit which is a unit of a monocyclic aromatic compound having a hydroxy group, the first unit of the bisarene compound is at least one selected from the group consisting of a unit of a bisphenol S compound and a unit of a bisphenol A compound, a molar ratio of the second units to a total amount of the first units and the second units is 10 mol % or more and 90 mol % or less.

2. 2. The lead-acid battery according to claim 1, wherein a total ratio (molar ratio) of the first unit and the second unit to a total amount of aromatic compound units contained in the first organic shrinkage regulator is 90 mol % or more.

3. The density of the negative electrode material is 3.3 g / cm 3 The lead acid battery according to claim 1 or 2.

4. The battery includes a positive electrode plate, a negative electrode plate, and an electrolyte solution. The negative electrode plate includes a negative electrode material, The negative electrode material includes an organic shrinkage preventer and a carbonaceous material, The organic shrinkage inhibitor includes a first organic shrinkage inhibitor, The first organic shrink-proofing agent includes a first unit which is a unit of a bisarene compound and a second unit which is a unit of a monocyclic aromatic compound having a hydroxy group, the first unit is at least one selected from the group consisting of a bisphenol S compound unit and a bisphenol A compound unit, The density of the negative electrode material is 3.3 g / cm 3 That's it, lead acid batteries.

5. The lead acid battery according to any one of claims 1 to 4, wherein the content of the carbonaceous material in the negative electrode material is 0.5 mass% or more.

6. The lead acid battery according to any one of claims 1 to 5, wherein the content of the carbonaceous material in the negative electrode material is 0.9 mass% or more.

7. The content of the organic shrink-proofing agent in the negative electrode material is 1 / m2 of the surface area of ​​the negative electrode material. 2 The lead acid battery according to any one of claims 1 to 6, wherein the weight average molecular weight is 1.8 mg or more per unit area.

8. The content of the organic shrink-proofing agent in the negative electrode material is 1 / m2 of the surface area of ​​the negative electrode material. 2 The lead acid battery according to any one of claims 1 to 7, wherein the lead acid content is 3.6 mg or less per unit area.

9. The content of the organic shrink-proofing agent in the negative electrode material is 1 / m2 of the surface area of ​​the negative electrode material. 2 The lead acid battery according to any one of claims 1 to 6, wherein the lead acid content is 1.5 mg or more and 3.8 mg or less per 1.5 mg.

10. The lead acid battery according to any one of claims 1 to 9, wherein the first unit includes at least a unit of a bisphenol S compound.

11. The lead acid battery according to any one of claims 1 to 10, wherein the second unit is a unit of a phenolsulfonic acid compound.

12. The lead acid battery according to any one of claims 1 to 11, wherein the sulfur element content of the first organic shrinkage inhibitor is 300 µmol / g or more and 9000 µmol / g or less.

13. The lead acid battery according to any one of claims 1 to 11, wherein the sulfur element content of the first organic shrinkage inhibitor is 300 µmol / g or more and less than 2000 µmol / g.

14. The lead acid battery according to any one of claims 1 to 12, wherein the sulfur element content of the first organic shrinkage inhibitor is 3000 µmol / g or more.

15. The lead acid battery according to any one of claims 1 to 14, wherein the weight average molecular weight (Mw) of the first organic shrinkage inhibitor is 7000 or more and 100,000 or less.

16. The lead acid battery according to any one of claims 1 to 15, wherein the ratio of the first organic shrinkage preventer to the total organic shrinkage preventer contained in the negative electrode material is 20 mass% or more.

17. The carbonaceous material includes at least one of a first carbonaceous material having a particle size of 32 μm or more and a second carbonaceous material having a particle size of less than 32 μm; The lead acid battery according to any one of claims 1 to 16, wherein the proportion of the second carbonaceous material in the entire carbonaceous material is 10 mass% or more and 100 mass% or less.

18. The lead acid battery according to any one of claims 1 to 17, wherein the content of the carbonaceous material in the negative electrode material is 0.1 mass% or more and 5 mass% or less.

19. The lead acid battery according to any one of claims 1 to 18, wherein the negative electrode material contains barium sulfate, and the content of the barium sulfate is 0.05% by mass to 3% by mass.

20. The density of the negative electrode material is 3.8 g / cm 3 The lead acid battery according to any one of claims 1 to 19, wherein:

Citation Information

Patent Citations

  • Liquid type lead acid battery

    JP2013161606A

  • Negative electrode plate for lead storage battery use, and method for manufacturing the same

    JP2014123525A

  • Lead storage battery

    JP2017079166A

  • Phenolic resin, electrode, lead storage battery and method of producing the same, and resin composition

    JP2017160326A

  • Control valve-type lead storage battery

    JP2018018742A